Взаимосвязь религиозной и государственной систем в древней Армении - Вардумян, Гоар Д. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In the Armenian Highlands, during the III-I mill. BC, various state formations emerged, each with its own religious and cult system that reflected the worldview, mythological thinking, and ideology of society. In Movses Khorenatsi’s “History of Armenia”, in the legends about Haykids, the transition from the pre-state era to the beginning of statehood is already evident.
Keywords: Древняя и средневековая история